AI-at-Scale Hinges on Gaining a 'Social License' - Candelon, François; di Carlo, Rodolphe; Mills, Steven (MIT Sloan Management Review, 2021)
For AI deployments to succeed, the systems must be trusted and accepted by those who use their input and those who are affected by the decisions these systems make or support. That means being accountable for the use and outputs of AI technologies, and transparently communicating both the benefits and drawbacks to all stakeholders. The authors describe the three sources of stakeholders' trust in artificial intelligence and suggest four steps companies can take to earn that trust.